Design, synthesis and antibacterial evaluation of a novel class of tetrahydrobenzothiophene derivatives. Issue 1 (5th December 2022) - Lai, Lin; Yang, Jinhua; Sun, Wanlin; Su, Xiaoyan; Chen, Jun; Chen, Xinan; Pei, Shuchen
Abstract : In this study, a new series of tetrahydrobenzothiophene derivatives have been designed. Abstract : In this study, a new series of tetrahydrobenzothiophene derivatives have been designed. Newly designed molecules have been synthesized through a medicinal chemistry route, and their characterization was done by using NMR and HR-MS techniques. Biological evaluation of the synthesized compounds has been done on Gram-negative and Gram-positive bacteria. The marketed antibiotics such as ciprofloxacin and gentamicin were used as controls. The in vitro evaluation results have shown that most of the targeted compounds exhibit good potency in inhibiting the growth of bacteria, including E. coli (MIC: 0.64–19.92 μM), P. aeruginosa (MIC: 0.72–45.30 μM), Salmonella (MIC: 0.54–90.58 μM) and S. aureus (MIC: 1.11–99.92 μM). In particular, compound 3b showed excellent activity with an MIC value of 1.11 μM against E. coli, 1.00 μM against P. aeruginosa, 0.54 μM against Salmonella, and 1.11 μM against S. aureus . From the results, a promising lead compound was identified for future development.